OVERPRESSURE ANALYSIS AND DISTRIBUTION IN SISI FIELD, KUTAI BASIN, EAST KALIMANTAN - FARISHY, REZA
The Sisi Field is a gas producing field in the Mahakam Delta which was discovered in 1986 and has been in production since 1992 until now. The production on this field has several obstacles, such as the occurrences of kick and loss when drilling in the overpressure zone. If overpressure is not well estimated, technical and financial losses can be large when production is carried out. The lithologies in the Sisi Field are dominated by fine-grained deposits. The fine-grained deposits will tend to form a closed system that will keep the pore fluid from dewatering and thus creating overpressure. The pore pressure analysis is carried out to determine overpressure zone, mechanism causing overpressure, and its distribution laterally and vertically. Pore pressure was analyzed by using wireline log, mud weight, pressure test, temperature, drilling reports, and vitrinite reflectance data. The geological condition of the study area is used as a reference to estimate pore pressure. Based on results of the analysis, overpressure zone is found in all wells. Overpressure zone in the Sisi Field starts from the depth of 3100 m below mean sea level. The result of well data analysis shows that there are three pore pressure patterns in the study area, i. e. hydrostatic zone, loading overpressure zone, and non-loading overpressure zone. Pore pressure value in loading overpressure zone ranges from 30-45 MPa, while the pore pressure in non-loading zone reaches 60 MPa at TD (Total Depth). The top of loading overpressure is located at FS6-2 to FS6-3 markers, while the top of non-loading overpressure is located at FS6-5 to FS6-8 markers. The top of overpressure are found to be shallower to the eastern and southern parts of the study area. Delta progradation and transgression process to the east and south during Middle Miocene – Late Miocene resulted in shallier environment to those parts and affected distribution of top of overpressure in the Sisi Field.